SERVICE QUALITY IMPROVEMENT EFFORTS RSU PKU MUHAMMADIYAH BANTUL SERVQUAL MODEL BASED - Utami, Endah (Jurnal Kesehatan Masyarakat (Journal of Public Health), 2012)
RSU PKU Muhammadiyah Bantul is one of the charities Muhammadiyah Persyarikatanbusiness located in the district of Bantul. In its efforts to enhancing the quality of service, themanagement did attempt to explore what the keinginkan customers. Steps taken bymanagement is to provide a suggestion box, but the attention of the customer against such amove does not show a meaningful response. This study aims to assist the hospital managementto explore the desires of customers based on SERVQUAL ModelSERVQUAL model of service quality measurement model is formulated byParasuraman. This model defines the gap or gap (G) for service quality factor. As for thedimensions of service quality used five dimensions of service quality developed byParasuraman et al, including the dimension Tangibles, Responsivness, Reability, Assuranceand EmphatyThe research results showed that all the attributes of the value gap. But once theperformance is quite satisfactory, it is seen from all the attributes of the service shows the valueabove 3. The efforts undertaken by the acquisition by the largest gap value in each dimension ofSERVQUAL, among others, prioritize budgetary allocations to the procurement of medicaldevices, training in terms of skills, attitudes and behavior conducted periodically bymanagement and pencermatan back towards the outsourcing of cleaning service in terms oftechnical coordinationKey words: Quality of service, the dimensions of quality, SERVQUAL